Scandcleft randomised trials of primary surgery for unilateral cleft lip and palate: 6. Dental arch relationships in 5 year-olds. Issue 1 (2nd January 2017) - Heliövaara, Arja; Küseler, Annelise; Skaare, Pål; Shaw, William; Mølsted, Kirsten; Karsten, Agneta; Brinck, Eli; Rizell, Sara; Marcusson, Agneta; Sæle, Paul; Hurmerinta, Kirsti; Rønning, Elisabeth; et al.
Abstract: Background and aim: Good dentofacial growth is a major goal in the treatment of unilateral cleft lip and palate (UCLP). The aim was to evaluate dental arch relationships at age 5 years after four different protocols of primary surgery for UCLP. Design: Three parallel randomised clinical trials were undertaken as an international multi-centre study by 10 cleft teams in five countries: Denmark, Finland, Sweden, Norway, and the UK. Methods: Three different surgical procedures for primary palatal repair (Arms B, C, D) were tested against a common procedure (Arm A) in the total cohort of 448 children born with non-syndromic UCLP. Study models of 418 patients (273 boys) at the mean age of 5.1 years (range = 4.8–7.0) were available. Dental arch relationships were assessed using the 5-year index by a blinded panel of 16 orthodontists. Kappa statistics were calculated to assess reliability. The trials were tested statistically with t- and Chi-square tests. Results: Good-to-very good levels of intra- and interrater reliability were obtained (0.71–0.94 and 0.70–0.87). Comparisons within each trial showed no statistically significant differences in the mean 5-year index scores or their distributions between the common method and the local team protocol. The mean index scores varied from 2.52 (Trial 2, Arm C) to 2.94 (Trial 3, Arm D). Conclusion: The results of the three trials do not provide statistical evidence that one technique is better than the others. Further analysis of the possible influence of individual surgical skill and learning curve are being pursued in this dataset. Trial registration: ISRCTN29932826.